Persistent racial and ethnic differences in location of death for children with cancer. Issue 8 (18th March 2015) - Cawkwell, Philip B.; Gardner, Sharon L.; Weitzman, Michael
Abstract : Background: Approximately one in 285 children will be diagnosed with cancer before reaching their 20th birthday. While both oncologists and parents report a preference that these children die at home rather than in a hospital, there are limited data exploring this issue in depth. Procedure: We performed a retrospective analysis of national‐level data from 1999 to 2011 from the National Center for Health Statistics "Underlying Cause of Death" database. Characteristics investigated included sex, race, age, ethnicity, cancer type, geographic location, and population density where the child lived. Results: Of the 2, 130 children with a death attributable to neoplasm in 2011, 37.6% (95% CI, 35.5–39.6%) died at home compared to 36.9% (95% CI, 35.0–38.8%) in 1999. In 2011, there were statistically significant racial differences between white, black, and Hispanic children across nearly every age group, with white children consistently most likely to die at home. Children of non‐Hispanic origin were significantly more likely to die at home than Hispanic children (40.3% vs. 29.3%, P  < 0.001). Children with CNS tumors are more likely to die at home than children with neoplasms as a whole, while children with leukemia are less likely. Statistically significant differences by race and ethnicity persist regardless of cancer type. Conclusions: There has been no significant change in the rate of children with cancer who die at home over the past decade. Racial and ethnic differences have persisted in end of life care for children with cancer with white non‐Hispanic children being most likely to die at home. Pediatr Blood Cancer 2015;62:1403–1408. © 2015 Wiley Periodicals, Inc.